METODOLOGI PENAFSIRAN KONTEKSTUAL ABAD 21: : Tawaran Tafsir Alquran Abdullah Saeed - zainuddin fanani; Juliansyah (Jurnal Penelitian Ilmiah INTAJ, 2019)
The reconstruction effort on interpretation continues to be carried out with various methods and approaches. This reflection then causes various Muslim and non-Muslim intellectuals to compete in interpreting Al-Qur'anic text. The purpose of this research is to find out Abdullah Saeed's contextual interpretation methodology in Al-Qur'an 21st Century. This research uses the book of Abdullah Saeed's entitled "Islamic Thought; An Introduction ", supported by other literature. In general, the four operational steps of Abdullah Saeed's contextual interpretation: 1) identifying initial considerations by understanding the subjectivity of the interpreter, constructing language and meaning and the world of the Al-Qur’an (encounter with the world of texts); 2) begin the task of interpretation by identifying the original intent of the text and believing the authenticity and reliability of the text (critical analysis of the text independently); 3) identify the meaning of the text by exploring each context (meaning for the first recipient; 4) linking the interpretation of the text to the current context (the contextualization process, the meaning for the moment). If the Al-Qur'an is said to be "according the time and place" the understanding is not what is written in the Al-Qur'an carried out anytime and anywhere, but must be adapted to space and time. This does not reduce the degree of Al- Qur'an, but makes the benefit of the people.